Nurse educators clinical skill competence in Ethiopia: A phenomenological study - Agezegn Asegid; Nega Assefa; Tesfaye Assebe Yadeta; Tegbar Yigzaw; Biftu Geda (Elsevier, 2023)
Background: Though literature focuses on how nurses become an educator and assume the educator's role, little is known about their experience in relation to clinical skill competencies. Thus, the main aim of this study was to explore nurse educators' experience of clinical skill competencies after assuming educator role. Methods: A descriptive phenomenological study was conducted on twelve purposely selected nurse educators in Ethiopian public universities from September to December 2021. Their prior clinical teaching experience (>=5years) and total teaching experience (>=5years) were taken as selection criteria. Colaizzi's seven-step analysis method was applied. Results: This study included four female and eight male nurse educators. Their clinical teaching experience ranged from 6 to 14 years, with an average of 11.2 years. Five of the participants had never worked in a clinical setting before becoming clinical educators. The experience of a nurse educator's clinical skill competencies identified four themes and 24 sub-themes. The themes include; (1) Feelings of incompetence (2) Seeking Support (3) Self-development (4) Decline of clinical skills. Conclusion: Nurse educators in Ethiopia have been working through difficult conditions to obtain and maintain clinical skill competency. This is related to a poor role transition strategy, a lack of adequate clinical engagement and a lack of systems level support to sustain clinical competence. We recommend launching a full-time clinical educator training program; school-service integrations; the development of a mandatory continuing professional development activity; and regulating the educational activity.